STEAM Approach Focusing on Natural Sciences and Geometry in the Proliferation of Pigeons - Roberia Silva da Penha Lourenço; Raíza de Araújo Domingos Soares; Dennys Leite Maia (Universitas Negeri Surabaya, 2025)
This paper aims to analyze the STEAM approach in teaching Natural Sciences and Geometry in a Brazilian school. It is an excerpt from a study conducted with a view to disseminating investigative and creative pedagogical practices in K-12 Education. The teaching experience based on the STEAM approach, which is the focus of this article, explored the problem of the proliferation of pigeons in the surroundings of the school community identified by the students themselves. The scientific methodology applied in this study was Action Research, of a qualitative and exploratory nature. The data sources were the logbook, questionnaires, multimedia recordings and the productions developed throughout the investigative and creative practice. The research was developed in a peripheral school in Natal/RN, in northeast Brazil, in a second-year high school class with 32 students, in which the study of Geometry was planned for the entire school year. The results showed that the integration of STEAM areas, such as pedagogical practices in combating the proliferation of pigeons involving Mathematics, focusing on Geometry, and Natural Sciences, mobilized Hoffer's (1981) skills and critical thinking, collaboration, communication and creativity, as well as providing opportunities for student protagonism. It is concluded that the STEAM approach placed the student at the center of the learning process and provided opportunities for the mobilization of cognitive and socio-emotional skills in an application relevant to the school community chosen by the students.